English Language Learning Model Training Based on ICT through Web-Based Learning in Subject Teacher Consultation Groups (MGMP) in Rokan Hulu Regency - Sukma, Dian (Indonesian Journal of Advanced Research, 2026)
This community service project aimed to enhance English teachers’ competencies in integrating Information and Communication Technology (ICT) into teaching through web-based learning. The program was conducted for members of the Subject Teacher Forum (MGMP) in Rokan Hulu Regency, involving 44 participants consisting of teachers and school staff. The training focused on developing basic knowledge and practical skills in creating and managing blogs as interactive learning media using platforms such as WordPress. The methods employed included lectures, hands-on practice, discussions, and pre-test and post-test evaluations. The results indicated a significant improvement in participants’ understanding of website-based learning, as shown by increased post-test scores compared to pre-test results. The training successfully stimulated participants’ creativity and ability to develop and publish instructional materials online. It is expected that participants will further implement and disseminate these skills to improve the quality of teaching and learning processes. Continued training is recommended to deepen participants’ competencies in ICT-based education.